Prevalence of malnutrition risk among older French adults with culinary dependence. (20th October 2021) - Van Wymelbeke-Delannoy, Virginie; Maître, Isabelle; Salle, Agnès; Lesourd, Bruno; Bailly, Nathalie; Sulmont-Rossé, Claire
Abstract: Objective: The term 'culinary dependence' denotes a situation in which someone delegates all or part of their daily meal-related activities to a third party. The present study aimed to explore nutritional risk among older people (≥65 years) with culinary dependence. Method: The first survey included 559 people either living at home without help, with help unrelated to food activities, with help related to food activities or living in nursing home. The second survey included 319 people with food help provided by a caregiver, by meals-on-wheels or by a nursing home. Nutritional status was assessed with the Mini-Nutritional Assessment. Sociological background and wellness variables (health, cognitive and mental status) were collected. Results: The first survey found a strong association between culinary dependence and nutritional risk. About half of the people who delegated their food-related activities were malnourished or at risk of malnutrition compared with only 4% for people with no help and 12% for people with help unrelated to food activity. According to the second survey, this prevalence varied slightly depending on who the tasks were delegated to (46% for those who had the support of a caregiver; 60% for those who used a meals-on-wheels service; 69% for those living in nursing home). According to multivariate analyses, dependence categories, depressive symptoms and cognitive status were identified as independent determinants of malnutrition. Conclusion: Without inferring a causal relationship between dependence and malnutrition, there is a strong need for care structures to take into account the issue of malnutrition when developing services targeting older people.